Patterns of patient withdrawal from BCG treatment for bladder cancer: A retrospective time interval analysis. Issue 2 (2nd May 2019) - Alcorn, Jason; Burton, Rob; Topping, Annie
Abstract: The research aim of this research was to answer the questions of what were the patterns that have been recorded for the withdrawal from BCG treatment and what individual factors influenced the withdrawal? Bacillus Calmette‐Guerin (BCG) vaccine was first introduced at the turn of the 19th to 20th century and since the 1970s has become significant in the treatment of non‐muscle invasive bladder cancer (NMIBC). It is concerning to note that little is known about the patient experience of this intravesical treatment, which is particularly concerning. Despite over 50 years of clinical use, early withdrawal from treatment rates of between 32% and 86% have been reported in the literature. This study sought to estimate the rate of non‐completion of BCG regime in one English National Health Service Cancer Unit and identify factors that contributed to patients' decisions to withdraw. A retrospective observational time interval study of a consecutive sample 234 case records of patients who underwent intravesical BCG treatment in one English National Health Service Cancer Unit, using time to event analysis. The population for this review was from a large metropolitan area in England, including a large northern town and satellites where heavy industry had dominated. The overall withdrawal rate was 211 (90%) prior to completion of induction and maintenance regime. The majority, 107 (46%) withdrew from treatment within the first year. Age, number of side effects and symptoms and contact with CNS were all associated with withdrawal. The data has shown that age, side effects, contact details and information giving may be factors that contribute to a patient deciding whether they stay on treatment or withdraw from it.